PP.38.10: ASSESSMENT OF CENTRAL BLOOD PRESSURE AS A PREDICTOR OF TARGET ORGAN DAMAGE IN CHILDREN WITH PRIMARY HYPERTENSION. (June 2015) - Obrycki, L.; Niemirska, A.; Kulaga, Z.; Litwin, M.
Abstract : Objective: Central systolic blood pressure (cSBP) is assumed to be the best indicator of cardiovascular risk caused by elevated blood pressure. However, there are no data on usefulness of measurements of cSBP, augmentation pressure (AugP) and augmentation index (AugInd) in assessment of risk of target organ damage (TOD) in hypertensive children. The aim of study was to assess associations of noninvasive measurements of cBP, AugP and AugInd with left ventricular mass (LVMi) and carotid intima-media thickness (cIMT) in children with primary hypertension. Design and method: 114 children (26 girls) in mean age 15 ± 2.5 years referred because of elevated blood pressure and in whom secondary hypertension was excluded were included to the study. cSBP, central pulse pressure (cPP), AugP, AugInd, cardiac index (CI), total peripheral resistance index (TPRI) and pulse wave velocity (PWV) were measured with oscillometric method using Vicorder device. In all patients LVMi and cIMT was measured. Blood pressure status was defined according to ambulatory blood pressure measurement (ABPM) classification. Results: 44 children were normotensive, 18 were prehypertensive, 9 had ambulatory hypertension and 43 severe ambulatory hypertension. Children with severe ambulatory hypertension had significantly greater AugP, CI and carotid wall cross sectional area (WCSA) than normotensive children. TPRI was lower in children with severe ambulatory hypertension than in normotensive children. cSBP correlated with WCSA (p = 0.015; r = 0.255) and AugP with LVMi (p = 0.02; r = 0.220). Children with cSBP above and below 95 percentile did not differ regarding prevalence of left ventricular hypertrophy (LVH) and arterial injury. ABPM had greater sensitivity and specificity for predicting LVH than AoBP. For cIMT and WCSA increase both ABPM and AoBP had similar sensitivity and specificity. Conclusions: cSBP and AugP assessed non-invasively with oscillometric method correlated with markers of hypertensive TOD. Although sensitivity and specificity of cSBP and ABPM as predictors of arterial injury was similar, ABPM performed better as predictor of LVH.